Kerja sosial : artikel-artikel pilihan - Abd. Razak Abd. Manaf (Abdul Razak Abd. Manaf); Zakiyah Jamaluddin (Cheras, Kuala Lumpur : Utusan Publications & Distributors, 2002)
On social work to strengthen the quality of life in Malaysia; collection of articles.
Includes bibliographical references.
In Malay.
Keywords: Social service -- Malaysia; Malaysia -- Social conditions